2017
DOI: 10.1038/ncomms15346
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age-dependent APC/C-mediated decrease in securin causes premature sister chromatid separation in meiosis II

Abstract: Sister chromatid attachment during meiosis II (MII) is maintained by securin-mediated inhibition of separase. In maternal ageing, oocytes show increased inter-sister kinetochore distance and premature sister chromatid separation (PSCS), suggesting aberrant separase activity. Here, we find that MII oocytes from aged mice have less securin than oocytes from young mice and that this reduction is mediated by increased destruction by the anaphase promoting complex/cyclosome (APC/C) during meiosis I (MI) exit. Inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 44 publications
(89 reference statements)
2
38
0
Order By: Relevance
“…It was subsequently found that metaphase-II eggs from aged mice exhibit lower levels of securin, and that this reduction is likely explained by the loss of the SAC activity, which would normally moderate the Anaphase-Promoting-Complex/Cyclosome at the meiosis-I to meiosis-II transition. Accordingly, overexpression of securin in aged oocytes was able to partially prevent premature separation of sisters [124]. This striking observation potentially places a SAC deficiency upstream of the cohesion loss that is central to oocyte aneuploidy.…”
Section: Sac Decline?mentioning
confidence: 88%
“…It was subsequently found that metaphase-II eggs from aged mice exhibit lower levels of securin, and that this reduction is likely explained by the loss of the SAC activity, which would normally moderate the Anaphase-Promoting-Complex/Cyclosome at the meiosis-I to meiosis-II transition. Accordingly, overexpression of securin in aged oocytes was able to partially prevent premature separation of sisters [124]. This striking observation potentially places a SAC deficiency upstream of the cohesion loss that is central to oocyte aneuploidy.…”
Section: Sac Decline?mentioning
confidence: 88%
“…Indeed Nabti et al revealed that oocytes from aged mice destroy securin more rapidly and to a greater extent than oocytes from younger mice. As a consequence, separase inhibition in MII is incomplete in these cells and sister chromatid cohesion is lost prematurely resulting in segregation defects 57 .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study indicates that Smc1β is essential for activation of SAC activity during mouse oocyte meiosis [ 62 ]. Therefore, there might be some association between decreased kinetochore localization of the SAC proteins and cohesion loss with maternal age, including the possibility that decreased SAC ability in aged oocytes promotes the APC/C Cdc20 to degrade cyclin B1 and securin, which causes the loss of sister chromatid cohesion [ 63 ] ( Figure 2 A).…”
Section: The Cause Of Age-related Loss Of Cohesionmentioning
confidence: 99%